Empowerment of the PKK Women's Group in Tabing Jungle Village through the Introduction of Live Pharmacies and Self-Medication using Family Medicinal Plants - Herda Ariyani; Dewi Nurhanifah; Muhammad Anshari; Dieny Redha Rahmani (Borneo Community Development, 2021)
The Living Pharmacy is the use of land which is usually located in the yard of the house which is used to grow plants that have many benefits. Especially traditional medicine to cure the diseases suffered and can be treated by yourself without having to use drugs that contain chemicals that are sold in pharmacies. Empowerment of vacant land in the village environment aims to maintain the village environment so that it remains beautiful and can obtain useful results. This community service method is carried out face-to-face with PKK women in Tabing Rimbah Village with media in the form of booklets and also PPT. With the theme of Socializing How to Empower Life Pharmacies. use the pretest and posttest as a measure of participants' understanding of the information provided. And from the scores obtained, it can be seen that there is an increase in participants' understanding of the material that has been presented, in addition to the pretest and posttest, additional evaluations regarding TOGA are also given. Take advantage of TOGA for health. Apotek Hidup merupakan pemanfaatan tanah yang biasanya terletak di halaman atau di pekarangan rumah yang digunakan untuk ditanami berbagai tanaman yang mempunyai banyak khasiat. Khususnya obat tradisonal untuk menyembuhkan bermacam penyakit yang diderita dan bisa diobati sendiri tanpa harus menggunakan obat yang mengandung kimia yang dijual di apotek. Pemberdayaan lahan kosong dilingkungan desa bertujuan menjaga lingkungan agar senantiasa tetap asri dan bisa memperoleh hasil yang bermanfaat. Metode kegiatan pengabdian masyarakat ini dilakukan secara face to face langsung bersama ibu-ibu PKK di Desa Tabing Rimbah dengan media berupa Booklet dan juga PPT. Digunakan pretest dan posttes sebagai tolak ukur pemahaman peserta terhadap informasi yang diberikan. Berdasarkan hasil nilai yang didapatkan dapat terlihat bahwa ada peningkatan pemahaman peserta mengenai materi yang telah disampaikan. Selain pretest dan posttest, diberikan juga evaluasi tambahan mengenai TOGA, berdasarkan evaluasi dapat ditarik kesimpulan bahwa ibu-ibu PKK di desa Tabing rimbah sudah mulai membiasakan dalam menanam serta memanfaatkan TOGA untuk kesehatan.